The Degree of Availability of Nutrition Education Concepts in Kindergarten Curricula (The International Journal of Educational Sciences and Arts, 2025)
This research aimed to identify the degree of availability of nutritional education concepts in kindergarten curricula, by identifying a list of nutritional education concepts proposed to be included in kindergarten curricula, and measuring the degree of availability of nutritional education concepts in kindergarten curricula. The descriptive analytical approach was followed as an approach to the study, and a list of nutritional education concepts proposed to be included in kindergarten curricula, and a content analysis card for kindergarten curricula in the Kingdom of Saudi Arabia, were used as a research tool. The research sample consisted of the topics included in the kindergarten unit books of the national curriculum in the Kingdom of Saudi Arabia for the third level (5 years), which have been taught since the academic year (1444 AH/2023 AD). They are 5 books, namely: the Animals Unit, the Weather Unit, the Buildings Unit, Transportation unit, all about me unit. The results revealed that there is a set of nutritional education concepts proposed to be included in kindergarten curricula, which were represented in (22) sub-concepts, distributed among five main concepts, which are the importance of food (5), types of food and its sources (3), healthy nutrition (6), Preserving food (2), correct behaviors with food (5), and that the degree of availability of nutritional education concepts in kindergarten unit books for the national curriculum in the Kingdom of Saudi Arabia for the third level (5-years) taught since the academic year (1444 AH/2023 AD) is small. Very, it lacks the basic and necessary concepts related to food education. In light of the results, the researcher presented some recommendations and proposals.
Keywords: Nutrition Education Concepts; Kindergarten Curricula